Fish migration based on feeding or spawning of selected known marine species caught from the Bolusao and Poblacion rivers of Lawaan, Eastern Samar, Philippines. - Medrina, Rose Angeli M.; Dela Cruz, Margarita T. (Rose Angeli M. Medrina, 2018)
Based on the stomach content and gonadal stage analyses, most marine species caught from the Bolusao and Poblacion rivers, in the months of October and November 2017, and in January and February 2018, migrate to the river to feed. The recorded average salinity for the upstream, midstream and downstream were 0 ppt, 2.58 ppt, and 10.30 ppt respectively in Bolusao river, and 0 ppt, 5.75 ppt, and 22.80 ppt in Poblacion river, respectively. Two species, E. puntang and S. sihama were caught in Bolusao River. On the other hand, 14 species belonging to family Carangidae, Leiognathidae, Gerreidae, Pomacentridae, Lutjanidae, Mugilidae, Siganidae, Sillaginidae, and Sphyraenidae were caught in Poblacion River and were examined. Gut content analysis showed that E. puntang caught in Bolusao River fed mainly on Macoma sp. with 77.30% IRI. In Poblacion River, D. insidiator, G. erythrourus, H. plagiometopon, M. perusii, which are detrivores, had stomachs that were found to contain detritus mainly of fine sand and silt. Siganid species, S. fuscescens, S. guttatus and S. vermiculatus, which are herbivorous, had stomachs which contained digested plant materials. C. papuensis, L. fulviflamma, and S. sihama have shown carnivorous diet. L. fulviflamma was found to feed on crab, C. papuensis preyed dominantly on shrimp with 72% IRI, and S. sihama fed mainly on Lumbriculus sp. and fish scale with 34.55% IRI. Gonadal stage analysis has shown that marine species migrated also utilize the Bolusao and Poblacion rivers to spawn. In Bolusao River, an individual of S. sihama and E. puntang were caught spawning upstream and downstream respectively. While only five (5) species were caught spawning in midstream and downstream of Poblacion river.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.